CONTENT MANAGEMENT SYSTEM UNTUK ULOS BATAK TOBA - TEAMSAR MULIADI PANGGABEAN (JURNAL ILMIAH SIMANTEK, 2019)
Content Management System is a process in supporting the creation, management, dissemination, publication, and search for knowledge. Knowledge basically consists of tacit and explicit. Currently, knowledge relating to Ulos is spread in various sources, such as blogs, books, and news sites that contain Ulos content. Comparison between undocumented knowledge and already large enough. This knowledge that is not spread is in someone's person. In fact, people who know the ins and outs of Ulos are really very minimal. Ulos has high economic value and potential for Indonesia. Because the value and potential of Ulos is truly enormous, detailed knowledge of Ulos needs to be maintained. To maintain the preservation of Indonesian culture, this research intends to build a special content management system in Elos, so that all tacit and explicit knowledge can be documented in one source..